Characterization of Salmonella Resistome and Plasmidome in Pork Production System in Jiangsu, China - Liu, Qingxin; Chen, Wenjing; Elbediwi, Mohammed; Pan, Hang; Wang, Liqun; Zhou, Chuang; Zhao, Bin; Xu, Xinguo; Li, Dingguo; Yan, Xin; Han, Xiao; Li, Hanyuan; et al. (Frontiers in Veterinary Science, 2020)
The prevalence of antimicrobial resistance in zoonotic Salmonella is a significant ongoing concern over the world. Several researchers have investigated the prevalence of Salmonella infections in the farm animals in China; however, there is only limited knowledge about the Salmonella cross-contamination in the slaughterhouses. Moreover, the application of genomic approaches for understanding the cross-contamination in the food-animal slaughterhouses is still in its infancy in China. In the present study, we have isolated 105 Salmonella strains from pig carcasses and environment samples collected from four independent slaughterhouses in Jiangsu, China. All the Salmonella isolates were subjected to whole-genome sequencing, bioinformatics analysis for serovar predictions, antimicrobial resistance genes, and plasmid types by using the in-house Galaxy platform. The antimicrobial resistance of Salmonella isolates was determined using a minimal inhibitory concentration assay with 14 antimicrobials. We found that the predominant serovar and serogroup was S. Derby and O:4(B), with a prevalence of 41.9% and 55%, respectively. All the isolates were multidrug-resistant and the highest resistance was observed against antimicrobials tetracycline (95.4%) and trimethoprim and sulfamethoxazole (90.9%,). The dominant genotype was ST40, with a total of thirteen identified sequence types. The dominant plasmid and antimicrobial-resistant gene were IncFIB(K)-1-Kpn3 and acc(6’)-Iaa, respectively. Additionally, the colistin-resistant determinant mcr-1 gene was detected in five (4.8%) strains. Our study demonstrated the prevalence of antimicrobial resistance in Salmonella strains isolated from pig slaughterhouses in China and suggested that the genomic platform can serve as routine surveillance along with the food-chain investigation.